2023
DOI: 10.21203/rs.3.rs-2485920/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the relationship between plasma carnitine levels and non-valvular atrial fibrillation

Abstract: Objective To investigate the correlation between plasma carnitine levels and atrial fibrillation and its predictive value in atrial fibrillation by analyzing the changes of plasma carnitine levels in patients with atrial fibrillation (AF) by metabolomics methods. Methods The clinical data of consecutive patients with non-valvular atrial fibrillation admitted to the Second Hospital of Dalian Medical University from January 2020 to January 2022 and patients with sinus rhythm admitted for other reasons during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The studies indicated that the atrial diameters in the atrial fibrillation group were apparently greater than those in the SR group; Atrial tissue in the atrial fibrillation group has visible fibrosis changes; the relative expression of type I collagen mRNA (2 −ΔΔCt ) in the atrial muscle samples from patients with atrial fibrillation was markedly higher than that in patients with sinus rhythm. It is suggested that the occurrence and development of atrial fibrosis in patients with rheumatic valvular disease and atrial fibrillation may be related to the up-regulation of the transcription level of type I collagen gene, the increase of synthesis and secretion of type I collagen, which leads to the abnormal accumulation of collagen in atrial tissue and the imbalance of I/III collagen deposition ratio, which provides a pathological matrix for the occurrence and maintenance of atrial fibrillation [12] [13] [14]. Whether PDGF/PDGFR signal is involved in the occurrence, development and maintenance of atrial fibrosis due to valvular atrial fibrillation by up-regulating the transcription level of type I collagen gene, it leads to the increase of fibroblast synthesis and secretion of type I collagen, and abnormal accumulation of collagen in atrial tissue remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The studies indicated that the atrial diameters in the atrial fibrillation group were apparently greater than those in the SR group; Atrial tissue in the atrial fibrillation group has visible fibrosis changes; the relative expression of type I collagen mRNA (2 −ΔΔCt ) in the atrial muscle samples from patients with atrial fibrillation was markedly higher than that in patients with sinus rhythm. It is suggested that the occurrence and development of atrial fibrosis in patients with rheumatic valvular disease and atrial fibrillation may be related to the up-regulation of the transcription level of type I collagen gene, the increase of synthesis and secretion of type I collagen, which leads to the abnormal accumulation of collagen in atrial tissue and the imbalance of I/III collagen deposition ratio, which provides a pathological matrix for the occurrence and maintenance of atrial fibrillation [12] [13] [14]. Whether PDGF/PDGFR signal is involved in the occurrence, development and maintenance of atrial fibrosis due to valvular atrial fibrillation by up-regulating the transcription level of type I collagen gene, it leads to the increase of fibroblast synthesis and secretion of type I collagen, and abnormal accumulation of collagen in atrial tissue remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%